Does Internet-based cognitive behavioral therapy (iCBT) prevent major depressive episode for workers? A 12-month follow-up of a randomized controlled trial. Issue 9 (July 2015) - Imamura, K.; Kawakami, N.; Furukawa, T. A.; Matsuyama, Y.; Shimazu, A.; Umanodan, R.; Kawakami, S.; Kasai, K.
<x content-type="archive" xml:space="preserve">Abstract</x> Background In this study we investigated whether an Internet-based computerized cognitive behavioral therapy (iCBT) program can decrease the risk of DSM-IV-TR major depressive episodes (MDE) during a 12-month follow-up of a randomized controlled trial of Japanese workers. Method Participants were recruited from one company and three departments of another company. Those participants who did not experience MDE in the past month were randomly allocated to intervention or control groups (n = 381 for each). A 6-week, six-lesson iCBT program was provided to the intervention group. While the control group only received the usual preventive mental health service for the first 6 months, the control group was given a chance to undertake the iCBT program after a 6-month follow-up. The primary outcome was a new onset of DSM-IV-TR MDE during the 12-month follow-up, as assessed by means of the web version of the WHO Composite International Diagnostic Interview (CIDI), version 3.0 depression section. Results The intervention group had a significantly lower incidence of MDE at the 12-month follow-up than the control group (Log-rank χ2 = 7.04, p < 0.01). The hazard ratio for the intervention group was 0.22 (95% confidence interval 0.06–0.75), when estimated by the Cox proportional hazard model. Conclusions The present study demonstrates that an iCBT program is effective in preventing MDE in the working population. However, it should be noted that MDE was measured by self-report, while the CIDI can measure the episodes more strictly following DSM-IV criteria.